Understanding spin-evolution and super-orbital modulation of Ultraluminous X-ray pulsars - Vasilopoulos, G.; Ray, P.; Koliopanos, F.; Petropoulou, M.; Haberl, F.; Lander, S. (American Astronomical Society Meeting Abstracts #236, 2020)
Ultra luminous X-ray pulsars (ULXP) are fascinating objects, whose X-ray emission greatly exceeds the Eddington limit for a solar mass object. Given the coherent pulsations we now know that these systems host accreting magnetized Neutron Stars (NS), thus challenging our understanding of accretion theory. Moreover several of these systems show super-orbital variability where the observed flux change by factor more than 10. Key questions about the nature of these systems are; is there is beaming involved that enhances the derived isotropic Luminosity? What is the magnetic field of the NS in ULXPs and how this compares to the typical X-ray pulsars? and what is the nature of the super-orbital modulation? The study of individual ULXPS can help us answer these key questions. Here I will present observational constrains on the properties of NGC 300 ULX1. Through a year long X-ray monitoring we discovered that even when the X-ray flux of the system decreased by a factor of 20 the spin-up of the NS continues at a constant rate denoting constant mass accretion onto the NS. Moreover, I will discuss the changes in the observed flux in the context of a precessing disc and outflows. In addition, I will discuss the properties of newly confirmed ULXP M51 ULX7, I will show that outflows are not a necessary requirement to account for super orbital variability, and will discuss alternative mechanisms.